Expression and promoter methylation status of two DNA repair genes in leukocytes from patients undergoing propofol or isoflurane anaesthesia - Freire, Cristiana M.M. [UNESP]; Braz, Mariana Gobbo [UNESP]; Marcondes, João Paulo C [UNESP]; Arruda, Nayara M. [UNESP]; Braz, José Reinaldo C [UNESP]; Rainho, Cláudia A. [UNESP]; Braz, Leandro Gobbo [UNESP]; Salvadori, Daisy M.F. [UNESP] (Oxford University Press (OUP), 2018)
Despite the widespread use of the anaesthetics propofol (PROP) and isoflurane (ISO), data about their toxicogenomic potential and interference in epigenetic events are unknown. This study evaluated the expression and methylation profile of two important DNA-repair genes (XRCC1 and hOGG1) in 40 patients undergoing elective and minimally invasive surgery (tympanoplasty and septoplasty) under ISO or PROP anaesthesia.The endpoints were examined at three sampling times: before anaesthesia (T0), 2 h after the beginning of anaesthesia (T2) and 24 h after the beginning of surgery (T24). Both gene expressions were assessed by quantitative real-time polymerase chain reaction (qRT-PCR), whereas methylation specific-PCR (MS-PCR) evaluated the DNA methylation patterns. Increased expression of XRCC1 was observed at T2 only in the PROP group. On the other hand, hOGG1 and XRCC1 expressions were decreased at T24 in both groups. There were no statistical significant differences between the two anaesthetics at the respective sampling times. The methylation status of XRCC1 (methylated at T0) and hOGG1 (unmethylated at T0) remained unchanged in the three sampling times. In conclusion, this study showed modulations of hOGG1 and XRCC1 expression especially 1 day after elective surgery in patients undergoing PROP and ISO anaesthesia. However, the data indicated that methylation was not the mechanism by which the genes were regulated. More studies are warranted to further investigate the possible epigenetic mechanisms involved after exposure to anaesthetics.